1984
DOI: 10.1111/j.1559-1816.1984.tb02258.x
|View full text |Cite
|
Sign up to set email alerts
|

Violence in College Students' Dating Relationships1

Abstract: In a survey of 504 college students examining predictors of violence in heterosexual relationships, over half of both men and women had committed at least one physically violent act, and men more often than women reported having been the victims of such acts. Most respondents who reported some experience with violence had both committed and received it, were involved in relatively few different types of violence, and first experienced violence when a relationship had moved beyond the casual dating stage. Modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(77 citation statements)
references
References 30 publications
3
74
0
Order By: Relevance
“…In the workplace, sexual harassment is one means by which perpetrators exert their power to acquire desired outcomes or resources (e.g., Cleveland & Kerst, 1993;Thacker & Ferris, 1991). Similarly, several studies have shown that men who are sexually aggressive also tend to be aggressive nonsexually (e.g., Lim & Howard, 1998;Sigelman, Berry, & Wiles, 1984), and they cognitively connect sexuality and social dominance (Pryor, Lavite, & Stoller, 1993). From the target's perspective, women who have experienced unwanted sexual attention and coercion in the workplace have typically also endured general disparagement toward their gender (Fitzgerald et al, 1988(Fitzgerald et al, , 1995Schneider, Swan, & Fitzgerald, 1997).…”
Section: Articulating the Relationship Between Sexual Harassment And mentioning
confidence: 99%
“…In the workplace, sexual harassment is one means by which perpetrators exert their power to acquire desired outcomes or resources (e.g., Cleveland & Kerst, 1993;Thacker & Ferris, 1991). Similarly, several studies have shown that men who are sexually aggressive also tend to be aggressive nonsexually (e.g., Lim & Howard, 1998;Sigelman, Berry, & Wiles, 1984), and they cognitively connect sexuality and social dominance (Pryor, Lavite, & Stoller, 1993). From the target's perspective, women who have experienced unwanted sexual attention and coercion in the workplace have typically also endured general disparagement toward their gender (Fitzgerald et al, 1988(Fitzgerald et al, , 1995Schneider, Swan, & Fitzgerald, 1997).…”
Section: Articulating the Relationship Between Sexual Harassment And mentioning
confidence: 99%
“…Ryan [25] reported that men experience higher rates of victimization and women inflict more physical aggression on their partners. Some researchers have found no marked gender difference in the frequency of violence [26,27] and that courtship violence was usually mutual [4,28,29]. In the debate over the equivalence of gender violence, some researchers investigated the motivation and effect of violence.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Men with a higher level of dating violence acceptance were found to have higher sexist attitudes (Ryan, 1995;Sigelman, Berry &Wiles, 1984). In their studies conducted in Turkey and Brazil, Glick and his colleagues (2002) found a relationship between protective and hostile sexism and attitudes towards justification of violence against the partner.…”
Section: Introduce the Problemmentioning
confidence: 96%